Assessment of visual sub-competencies through Visual Rubrics: case studies based on the Common European Framework of Reference of Visual Competencies (CEFR-VC). Issue 3 (2nd October 2022) - Kárpáti, Andrea; Paál, Zsuzsanna
Abstract: In the second version of the Common European Framework of Reference for Visual Competence (CEFR_VC) discussed in this journal issue, the main competency dimensions: creation and reception are represented in 16 sub-competencies, with an overarching competence dimension of metacognition. Visual Rubrics (VRs) support the assessment process of visual competency through an in-depth understanding of the content and levels of competences developed in an art education programme. Activities and their quality are captured in symbolic visualizations (images and explanatory textual rubrics) that scaffold the learning path and turn the competence development process into a metacognitive experience. Based on the first version of the Common European Framework of Visual Literacy (CEFR-VL), VRs for secondary-level art education were successfully employed in five European countries as summative assessment tools. In Hungary, the VR development continued with the new version of the framework, the Common European Framework of Visual Competency (CEFR-VC to explore the adaptability of VRs in a variety of educational settings. The tool proved to be useful in formal, school-based education as well as in the informal educational environment of museums. In this article, we explain the structure and imagery of the VRs and discuss their reception by art educators.